Darier's disease and Schizophrenia- A case report (Kerala Journal of Psychiatry, 2021)
Darier's disease is a rare autosomal dominant genodermatosis. There is a specific mutation in the ATP2A2 gene on chromosome 12q. Several neuropsychiatric manifestations have been described in association with Darier's disease.  Most reports have come from western populations, with limited reports of Darier's disease and its neuropsychiatric associations among Asian people, although the demographic and clinical profiles are comparable. We present a case of 38 year old female from Kerala with Darier's disease presenting with schizophrenia spectrum disorder. Her first degree relatives have schizophrenia-like psychosis and dermatological manifestations suggestive of Darier's disease.
Keywords: Darier's disease; Schizophrenia